INFLUENCE OF TECHNOLOGY ENHANCED LANGUAGE LEARNING (TELL) FOR MINORITY LANGUAGE PRESERVATION AND TEACHING EFFORTS FROM STUDENTS’ AND TEACHERS’ PERCEPTIONS - Alaa Abdul Azeem Abdul Abbass (Scholars Digest Publishing, 2023)
Comprehensive educational technology is the widespread practice of development, design, management, utilization, and the overall evaluation process and learning resources. Furthermore, the process of blended learning, a system of learning management, and virtual classrooms are the technological processes that teachers are adapting now for language learning. The application of technology has also facilitated an individual’s language learning effectively. Prior studies have outlined that the inception of technology has enabled teachers to imply classroom activities for effectively increasing the language learning process. The continuous development of technology has facilitated the teachers to develop their skills and facilitated the learning process for the students. The inception of technology has had a massive impact on the process of modern English language learning which has improved the vocabulary and language skills of the students. Presently, technologies have been considered one of the most complementary tools for teachers in the classroom, as they can positively impact the student’s learning outcomes.
Keywords: Technology, Practice, Development, Students, English Language Learning.